Skin fragility and wound management in Ehlers-Danlos syndromes: a report by the International Consortium on Ehlers-Danlos Syndromes and Hypermobility Spectrum Disorders Skin Working Group - Angwin, Chloe; Doolan, Brent J; Haußer-Siller, Ingrid; Labine, Barry; Lavallee, Mark; Mackay, Donald; Pope, F Michael; Seneviratne, Suranjith L; Winship, Ingrid; Burrows, Nigel P (Clinical and experimental dermatology, 2024)
The Ehlers-Danlos syndromes (EDSs) are a heterogeneous group of heritable connective tissue disorders characterized by joint hypermobility, skin hyperextensibility and generalized tissue fragility. In all types of EDS, skin wound healing is impaired to a variable degree. Additional support through wound management plans may help to improve these outcomes; however, there is a paucity of evidence regarding clinical management of skin fragility and wounds in EDS. This paper aims to review current evidence and provide recommendations for management of skin wounds in EDS types. Preventative measures to avoid skin injury are strongly recommended, including avoidance of high-impact sports and use of appropriate protection such as shin guards. Bruising is common, and some types of EDS are associated with haematoma formation, with management including compression bandages and consideration of pharmacological therapy. Skin fragility and tears should be managed with a focus on protection of remaining tissue, avoidance of wound tension and low-adherence dressings to avoid further injury. This paper provides clear recommendations to address skin management for this group of patients. It highlights the lack of good-quality published data to support treatment decisions.
Gesehen am 08.11.2024